2021
DOI: 10.3390/ani11061749
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fed Cattle Mobility during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic had significant consequences on cattle slaughter capacity in the United States. Although industry stakeholders implemented strategies to minimize cattle welfare impacts of increased weights, days on feed (DOF), and increasing temperatures, there were concerns that mobility challenges would be observed at slaughter facilities. The objectives of this study were to characterize mobility in fed cattle during this recovery period and to identify factors impacting mobility. A total of 158 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Cattle mobility and lameness are important considerations and have been focused on significantly more in recent years within the fed cattle industry, particularly in the United States (Edwards-Callaway and Calvo-Lorenzo, 2020). Mobility is a multifactorial issue impacted by not only weight, THI, sex, and days on feed (DOF; (Gonzaĺez et al, 2012;Edwards-Callaway et al, 2017;Martinez et al, 2021;Mijares et al, 2021), but also transportation (e.g., distance hauled) and lairage factors (e.g., lairage duration; Hagenmaier et al, 2017). One study within this review, however, reported a rather low prevalence of lameness (0.7%; Burgstaller et al, 2022) compared to other studies ranging from as low as 1.1% to 54.8% of cattle reported as clinically lame (Dudley, 2017), likely because the sample size of this study consisted of mostly young bulls and calves rather than older cattle.…”
Section: Health and Injurymentioning
confidence: 99%
“…Cattle mobility and lameness are important considerations and have been focused on significantly more in recent years within the fed cattle industry, particularly in the United States (Edwards-Callaway and Calvo-Lorenzo, 2020). Mobility is a multifactorial issue impacted by not only weight, THI, sex, and days on feed (DOF; (Gonzaĺez et al, 2012;Edwards-Callaway et al, 2017;Martinez et al, 2021;Mijares et al, 2021), but also transportation (e.g., distance hauled) and lairage factors (e.g., lairage duration; Hagenmaier et al, 2017). One study within this review, however, reported a rather low prevalence of lameness (0.7%; Burgstaller et al, 2022) compared to other studies ranging from as low as 1.1% to 54.8% of cattle reported as clinically lame (Dudley, 2017), likely because the sample size of this study consisted of mostly young bulls and calves rather than older cattle.…”
Section: Health and Injurymentioning
confidence: 99%
“…The author has observed in many U.S. beef plants that lameness in beef cattle has increased (Grandin, 2021). A recent survey by Mijares et al, 2021, indicated that 25% of U.S. feedlot cattle were lame. Increased body weight is associated with increased lameness (Marti et al, 2021).…”
Section: 1mentioning
confidence: 99%
“…In the U.S., the percentage of lame grain-fed cattle has increased. In 2020, only 74.5% of grain-fed beef cattle were free of lameness [13]. These data were collected during the months of July to October on 16,262 fed feedlot cattle that arrived at a large abattoir located in the Central Plains of the U.S.…”
Section: On-farm Factors Associated With Handling Problems At the Abattoirmentioning
confidence: 99%
“…This area is in the heart of the U.S. feedlot industry. In the previous years of 2016-2019, 96.19% to 89.32% of the fed feedlot cattle that arrived at an abattoir were free of lameness [13]. There are also some dairies with high percentages of lame cows.…”
Section: On-farm Factors Associated With Handling Problems At the Abattoirmentioning
confidence: 99%